Genetic Parameter Estimation of Rambutan Seedling Morphologicaltraits For A Better Rootstock Performance - Panjisakti Basunanda; Siswandono Siswandono; Nasrullah Nasrullah (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2000)
-